Tidal effects on water quality at the Pahang River - Syazwana, Muhamad (2019)
Water quality of surface water such as rivers and lakes are the common issues discussed in Malaysia. Due to hasty growing human population and development process, water quality of rivers including Pahang River was deteriorated. Consequently, human access to clean and safe water become a tremendous challenge. Earth rotation and gravitational force exerted by the moon may also influence the water quality. This study was focused on analysis of tidal effect on water quality at the Pahang River. The objectives were to determine the water quality of the Pahang River based on six parameters (BOD, COD,DO, AN, SS and pH) and to classify the Pahang River accordance to the Water Quality Index (WQI) during low tide and high tide from 2008 to 2017. Two stations, 4PH01 and 4PH17 were chosen due to their proximity the river mouth in order to observe the influence of tidal to the water quality at the Pahang River. The results of water quality trends shows the WQI of the Pahang River for the ten years sampling data mostly was in Class II. According to Department of Environment, DOE (2016), Class II of river were suitable for fishery II, water supply II and for recreational use with body contact. Analysis of six parameters shows there was no specific trend for all of them at both stations. The study concluded that there was no significant effects of the tidal to the WQI at both stations due to the distance of these stations are 12.56 km and 56.71 km from the river mouth. This study provides and widen the community knowledge on the pollution of the Pahang River and its current situation based on WQI and expected to raise awareness among society either the public authorities, industrial players or community who lives within the basin about the causes and sources that contribute to water pollution in the Pahang River and can figure out the best solution to prevent further deterioration of the river in future.